Preferences for a good death: a cross-sectional survey in advanced cancer patients. Issue Volume 12:Issue e4(2022) (3rd April 2019) - Hou, Xiaoting; Lu, Yuhan; Yang, Hong; Guo, Renxiu; Wang, Yun; Wen, Lihong; Zhang, Yaru; Sun, Hongyu
Abstract : Objective: The aim of this study was to describe preferences for a good death among Chinese patients with advanced cancer and then to explore factors contributing to their preferences including patient demographics and disease variables. Methods: A convenience sample of 275 patients with advanced cancer was recruited from a tertiary cancer hospital in Beijing, China, between February and December 2017. A Chinese version of the Good Death Inventory (GDI) was used to measure patients' preferences for dying and death. Besides, data were collected using a multi-itemed questionnaire focusing on demographic and disease characteristics of patients. Results: Of the 275 questionnaires returned, 248 responses were analysed (effective response rate 90.2%). According to the total scores for each of the 20 domains, the five most important domains of a good death were: good relationship with family (19.80±2.39), independence (19.66±2.56), maintaining hope and pleasure (19.56±2.55), good relationship with medical staff (18.92±3.73), not being a burden to others (18.89±3.30). Patients' characteristics including age, educational status, religious belief, medical payment types, family economic status, past experiences of the death of others, the period since cancer diagnosis, past experiences of hospitalisation and subjective physical condition influenced their preferences for a good death (all p<0.05). Conclusions: We had an in-depth knowledge and understanding of their preferences for good death among Chinese patients with advanced cancer. Meanwhile, we found some patients' factors contributed to different preferences for a good death. These findings have the potential to guide hospice care services aimed at achieving a good death for patients with advanced cancer.